2021
DOI: 10.1111/os.13139
|View full text |Cite
|
Sign up to set email alerts
|

Elution and Biomechanical Properties of Meropenem‐Loaded Bone Cement

Abstract: Objective: To investigate the biomechanical and elution properties of meropenem-loaded bone cement.Methods: Bone cement (Palacos LV) with 5% (2 g/4 0g), 10% (4 g/40 g), and 15% (6 g/40 g) meropenem; 5%(2 g/40 g) and 10% (4 g/40 g) vancomycin; and blank bone cement were prepared in a total of six groups named A2, A4, A6, B2, B4, and A0 (antibiotic-free). 36 cylinder specimens (6-mm diameter and 12-mm height) of all six groups were molded for a compression test. After the compression test, because of mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Risk factors for peri-spacer fractures include loose spacers, knee varus or valgus malignments, femoral notching, and poor bone quality around the spacer [ 10 ]. Antibiotic choice also affects the biomechanical properties of cement, with vancomycin-loaded bone cement showing favorable properties over cephazolin-loaded bone cement and meropenem-loaded bone cement demonstrating excellent biochemical properties [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for peri-spacer fractures include loose spacers, knee varus or valgus malignments, femoral notching, and poor bone quality around the spacer [ 10 ]. Antibiotic choice also affects the biomechanical properties of cement, with vancomycin-loaded bone cement showing favorable properties over cephazolin-loaded bone cement and meropenem-loaded bone cement demonstrating excellent biochemical properties [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al reported that bone cement remains above the 70 MPa threshold with the addition of up to 6 g of meropenem per 40 g of cement. However, the addition of vancomycin at 2 g/40 g and 4 g/40 g did not retain the 70 MPa threshold 23 . Another study by Slane et al investigated the addition of tobramycin and vancomycin individually and in combination with bone cement.…”
Section: Discussionmentioning
confidence: 99%